Pharmacogenomic tests of oncology drugs at Instituto Nacional de Câncer (INCA) - Guilherme Suarez-Kurtz (Brazilian Journal of Oncology)
The implementation, current status and future perspectives of the pharmacogenetics/genomics (PGx) testing program developed at Instituto Nacional de Cancer (INCA) are presented. Initial selection of drug-gene pairs for PGx testing was based on clinically-validated PGx associations and availability of international guidelines with PGx-informed dosing recommendations. The selected pairs were fluoropyrimidines-DPYD, irinotecan-UGT1A1, and thiopurines-TPMT/NUDT15. The aims and rationale for the implemented PGx tests, frequency of the interrogated genetic variants and assigned metabolic phenotypes, and the individual dosing recommendations are reviewed. Planned developments, such as collaboration with other cancer treatment centers, testing of additional drug-gene pairs (e.g., tamoxifen-CYP2D6), and inclusion of PGx testing in the routine workout of targeted patients at INCA were impacted by the outbreak of the COVID-19 pandemics. The Brazilian Society of Clinical Oncology is invited to play a leading role in the evaluation of the clinical utility of PGx tests of germline variants for oncology drugs in Brazil.